Celebracja sakramentu małżeństwa według wybranych dyrektoriów duszpasterstwa rodzin - Adamczyk, Jerzy (Ius Matrimoniale, 2016)
This article is dedicated to the celebration of marriage according to selected directories of ministry of families. Mentioned documents devote a lot of place to the rites of the marriage. In the first part of the article there were presented theological and pastoral meaning of the celebration of marriage. The second part pointed out preparations to marriage. The third part tells about ways of marriage celebration and in the last part there were discussed the place and the time of wedding.